Detection of Gene Alg8 and Alg44 in Clinical Isolates Pseudomonas Aeruginosa using Plymerase Chain Reaction Method - Didik Wahyudi; Wimpy Wimpy; Dewi Saroh (Indonesian Journal of Global Health Research, 2022)
The alg8 and alg44 genes are one of the genes that control alginate production in Pseudomonas aeruginosa bacteria, these genes are one of the main virulence factors causing chronic infections in the human body. Pseudomonas aeruginosa is a bacterium that causes infections in several cases in various parts of the body. The purpose of this study was to detect the presence of alg8 and alg44 genes in several isolates of Pseudomonas aeruginosa from several clinical samples (urine, sputum, and pus) using the Polymerase Chains Reaction method. The study was initiated by characterizing and purification of 6 isolates of Pseudomonas aeruginosa from urine, sputum, and pus samples (2 isolates each), identification of isolates was carried out by biochemical tests. Bacterial DNA isolation was carried out using the DNeasy Blood and Tissue Kit, the results of the isolation were tested by electrophoresis. Six samples of Pseudomonas aeruginosa DNA were tested for the presence of alg8 and alg44 genes by PCR method. The primary design was carried out using the website https://www.ncbi.nlm.nih.gov. The alg8 gene as a whole consists of 1214 nitrogenous bases, the primer used produces an amplicon of 882 bp (72.6%), alg44 gene consists of 818bp, the primer used amplifies 316 bp (36%). alg8 and alg44 genes were found in all isolates of Pseudomonas aeruginosa.